Sustained Response After Remdesivir and Convalescent Plasma Therapy in a B-Cell–Depleted Patient With Protracted Coronavirus Disease 2019 (COVID-19). (26th October 2020) - Malsy, Jakob; Veletzky, Luzia; Heide, Janna; Hennigs, Annette; Gil-Ibanez, Ines; Stein, Alexander; Lütgehetmann, Marc; Rosien, Ulrich; Jasper, Dorothea; Peine, Sven; Hiller, Jens; Haag, Friedrich; et al.
Abstract: We provide detailed clinical, virological, and immunological data of a B-cell–depleted patient treated with obinutuzumab for follicular lymphoma with protracted coronavirus disease 2019 (COVID-19) and viremia. A sustained response was achieved after 2 courses of remdesivir and subsequent convalescent plasma therapy. Immunocompromised patients might require combined and prolonged antiviral treatment regimens.